Estudio de cartera de ventas por línea de negocio del centro de producción Montalvo de Incubandina S.A. - Arguello Guerrero, Angela Ahikel (2021)
The research that was reflected in the development of this document was based on the Study of the Sales Portfolio by Business Lines of the Montalvo Production Center of the Incubandina S.A Company; Ecuadorian poultry company. The report was made through the application of technical tools such as the interview with the operational manager. In addition to the interview that was conducted, the company provided us with the information requested to finalize this report. Each company currently keeps a record of all its sales through manual or electronic invoicing; these documents allow the company to have proof of income. Therefore, the non-existence of these was detrimental to Incubandina S.A in 2020, in which its decrease in income from the sale of chicks was reflected. The purpose of the work was to determine if the company's sales portfolio increases or decreases; to reach this point, a comparison was made of the client portfolio for the years 2019 - 2020. A table was also made showing the income from the sales of the chicks and chicks of each brand belonging to the light and heavy lines.